1980
DOI: 10.1111/j.1432-1033.1980.tb04482.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of Annelid Erythrocruorins. Extracellular Hemoglobin of Arenicola marina (Polychaeta)

Abstract: The respiratory protein, erythrocruorin, of the annelid Arenicola marina was investigated. Spectral properties show many analogies with those of vertebrate hemoglobine. 144 heme groups (ferroprotoporphyrin) were found in the whole molecule, which has a relative molecular mass of 3.56 x lo6, as determined by sedimentation equilibrium, and an isoelectric point of 4.69. Protein dissociation patterns were analysed by electrophoresis after denaturation in the presence of dodecylsulfate, with and without 2-mercaptoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…The molecular mass found for Arenicola HBL Hb by MALLS (3648 -C 24 kDa) is in good agreement with the most recently published values of 3740 t-120 kDa and 3560 ? 40 kDa, respectively [21, 201. On the whole, our SDSIPAGE results on reduced Arenicola Hb are in good agreement with previous studies (20,21,241. However, we obtained a high resolution thus clearly revealing four components around 14100-16400 Da, whereas two of the earlier works found only two [20] and three [21] components.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The molecular mass found for Arenicola HBL Hb by MALLS (3648 -C 24 kDa) is in good agreement with the most recently published values of 3740 t-120 kDa and 3560 ? 40 kDa, respectively [21, 201. On the whole, our SDSIPAGE results on reduced Arenicola Hb are in good agreement with previous studies (20,21,241. However, we obtained a high resolution thus clearly revealing four components around 14100-16400 Da, whereas two of the earlier works found only two [20] and three [21] components.…”
Section: Discussionsupporting
confidence: 82%
“…40 kDa, respectively [21, 201. On the whole, our SDSIPAGE results on reduced Arenicola Hb are in good agreement with previous studies (20,21,241. However, we obtained a high resolution thus clearly revealing four components around 14100-16400 Da, whereas two of the earlier works found only two [20] and three [21] components. El Idrissi Slitine and Toulmond [24] also found four polypeptide chains by IEFIPAGE, and they concluded that the polypeptide chains A and B were of the same molecular mass but different isoelectric points.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The peripheral location of subunit M is in harmony with the well-known fact that the dissociation of Lumbricus Hb at alkaline pH gives two fractions, one consisting of subunit M and the other of subunits D1, D2, and T (7). Such a pattern of dissociation at alkaline pH has been observed for many annelid hemoglobins, including those of the oligochaetes, Tubifex (19,20) and Eisenia (21); the polychaetes Abarenicola (22), Arenicola (23)(24)(25), and Ophelia (26); and the leeches Haemopis (27) and Dina (28).…”
Section: Methodsmentioning
confidence: 66%